2022
DOI: 10.1007/s12687-022-00596-x
|View full text |Cite
|
Sign up to set email alerts
|

Multisite assessment of the impact of a prenatal testing educational App on patient knowledge and preparedness for prenatal testing decision making

Abstract: In this study, we wanted to assess the impact of the use of a patient educational app on patient knowledge about noninvasive prenatal testing (NIPT) and preparedness for prenatal screening decision-making. A randomized control study was carried out at three international sites between January 2019 and October 2020. Study participants completed a pre-consultation survey and post-consultation survey to assess knowledge, satisfaction, and preparedness for prenatal screening consultation. Providers completed a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition to increasing the number of clinical geneticists, certified genetic counselors, and obstetricians/ gynecologists with GC training in prenatal genetic testing, it may be necessary to train midwives and obstetric nurses immediately to provide primary information of prenatal testing, considering the daily clinical workflow in obstetrics. In addition, the usefulness of software applications for a better understanding of NIPT has been demonstrated at the global level, 26 and it will be essential to utilize these technologies for GC in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing the number of clinical geneticists, certified genetic counselors, and obstetricians/ gynecologists with GC training in prenatal genetic testing, it may be necessary to train midwives and obstetric nurses immediately to provide primary information of prenatal testing, considering the daily clinical workflow in obstetrics. In addition, the usefulness of software applications for a better understanding of NIPT has been demonstrated at the global level, 26 and it will be essential to utilize these technologies for GC in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous studies conducted in developed countries. [14][15][16] The result underlines the importance of pretest genetic counseling for all pregnant women as this facilitates understanding before decision-making. Importantly, this study showed that having an animated educational video added yielded a stronger effect on increasing knowledge of the screening's performance and limitations than traditional counseling alone.…”
Section: Discussionmentioning
confidence: 99%
“…13 Reports from developed countries have found that various tools in prenatal genetic counseling, such as educational apps and videos as well as low literacy decision aids, can improve the knowledge of pregnant women who undergo cell-free DNA screening. [14][15][16] However, data are limited from Thailand and other developing countries where women have different baseline socio-educational backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Women should not feel pressured but be enabled to make a decision based on their own beliefs. Therefore, it seems crucial to consider the development of standardised information in the form of booklets or online educational tools for patients [ 42 ]. This could facilitate access to detailed written information, in addition to verbal information provided during the consultation.…”
Section: Discussionmentioning
confidence: 99%